Isolation of Human Adipose‐Derived Stromal Cells Using Laser‐Assisted Liposuction and Their Therapeutic Potential in Regenerative Medicine. (9th September 2013) - Chung, Michael T.; Zimmermann, Andrew S.; Paik, Kevin J.; Morrison, Shane D.; Hyun, Jeong S.; Lo, David D.; McArdle, Adrian; Montoro, Daniel T.; Walmsley, Graham G.; Senarath-Yapa, Kshemendra; Sorkin, Michael; Rennert, Robert; et al.
Abstract : This study examined the impact of laser‐assisted liposuction on the quality and differentiation potential of adipose‐derived stromal cells (ASCs). It was found that laser‐assisted liposuction negatively impacts the biology of ASCs, and therefore cell harvest using suction‐assisted liposuction is preferable for tissue‐engineering purposes. Abstract : Harvesting adipose‐derived stromal cells (ASCs) for tissue engineering is frequently done through liposuction. However, several different techniques exist. Although third‐generation ultrasound‐assisted liposuction has been shown to not have a negative effect on ASCs, the impact of laser‐assisted liposuction on the quality and differentiation potential of ASCs has not been studied. Therefore, ASCs were harvested from laser‐assisted lipoaspirate and suction‐assisted lipoaspirate. Next, in vitro parameters of cell yield, cell viability and proliferation, surface marker phenotype, osteogenic differentiation, and adipogenic differentiation were performed. Finally, in vivo bone formation was assessed using a critical‐sized cranial defect in athymic nude mice. Although ASCs isolated from suction‐assisted lipoaspirate and laser‐assisted lipoaspirate both successfully underwent osteogenic and adipogenic differentiation, the cell yield, viability, proliferation, and frequency of ASCs (CD34 + CD31 − CD45 − ) in the stromal vascular fraction were all significantly less with laser‐assisted liposuction in vitro ( p < .05). In vivo, quantification of osseous healing by micro‐computed tomography revealed significantly more healing with ASCs isolated from suction‐assisted lipoaspirate relative to laser‐assisted lipoaspirate at the 4‐, 6‐, and 8‐week time points ( p < .05). Therefore, as laser‐assisted liposuction appears to negatively impact the biology of ASCs, cell harvest using suction‐assisted liposuction is preferable for tissue‐engineering purposes.